Multiple Small Bowel Intussusceptions Detected by Diagnostic Laparoscopy in an Adult Patient with Previously Undiagnosed Coeliac Disease - Saliu, Valon; Ulusoy, Cemal; Nikolovski, Andrej (SMC Media, 2022)
Enteric intussusception in adults is usually associated with the presence of a lead point seen on abdominal computerized tomography. However, as intussusception in coeliac disease may not have a lead point, a surgical procedure is often indicated in order to exclude small bowel tumour. We present the case of a male patient who presented with asymptomatic small bowel intussusception. During exploratory laparoscopy, five enteric intussusceptions were detected and a suspicion for coeliac disease was raised. Postoperative duodenal biopsy and CD3 immunohistochemical staining confirmed the diagnosis of coeliac disease, Marsh type 1.